Unconventional monetary policy and the great recession - Estimating the impact of a compression in the yield spread at the zero lower bound - Christiane Baumeister; Luca Benati (European Central Bank (ECB), 2010)
We explore the macroeconomic impact of a compression in the long-term bond yield spread within the context of the Great Recession of 2007-2009 via a Bayesian time-varying parameter structural VAR. We identify a `pure' spread shock which, leaving the short-term rate unchanged by construction, allows us to characterise the macroeconomic impact of a compression in the yield spread induced by central banks' asset purchases within an environment in which the short rate cannot move because it is constrained by the zero lower bound. Two main findings stand out. First, in all the countries we analyse (U.S., Euro area, Japan, and U.K.) a compression in the long-term yield spread exerts a powerful effect on both output growth and inflation. Second, conditional on available estimates of the impact of the FED's and the Bank of England's asset purchase programmes on long-term government bond yield spreads, our counterfactual simulations indicate that U.S. and U.K. unconventional monetary policy actions have averted significant risks both of deflation and of output collapses comparable to those that took place during the Great Depression.
Keywords: E30; E32; 330; Bayesian VARs; Great Recession; Monte Carlo integration; policy counterfactuals; stochastic volatility; structural VARs; time-varying parameters; Öffentliche Anleihe; Zinsstruktur; Geldpolitik; Wirkungsanalyse; VAR-Modell; EU-Staaten; Großbritannien; Japan; USA